Eksplorasi Strategi Koping Pada Penderita Diabetes Melitus Tipe 2 - Mohamad Akbar Aizhar; Arthur Huwae (Universitas Malahayati, 2026)
ABSTRACT Individuals with type 2 diabetes mellitus face not only physical challenges but also psychological pressures such as stress, anxiety, and a decreased quality of life. This condition encourages patients to use both adaptive and maladaptive Coping strategies in order to endure their illness. This study aims to explore how individuals with type 2 diabetes mellitus cope with stress and pressure caused by their illness through Coping strategies. The research used a qualitative approach with an interpretative phenomenological method, involving five participants aged 40–60 years who had been diagnosed with type 2 diabetes mellitus and reported experiencing stress. Data were collected through in-depth interviews and analyzed using Coping mechanisms, including problem-focused Coping, emotion-focused Coping, and religious Coping. The findings show that at the initial stage, participants tended to deny their condition and experienced negative emotions such as sadness, anger, and stress. Over time, however, they gradually moved toward acceptance by adjusting themselves and giving spiritual meaning to their illness. The Coping strategies used included problem-focused efforts such as regular medical treatment and maintaining a healthy lifestyle, emotion-focused efforts such as crying, surrendering, and seeking support, as well as religious Coping such as praying, attending religious gatherings, performing worship, and interpreting the illness as a test from God. Support from family, spouses, friends, and life experiences played an important role in strengthening psychological resilience.These findings suggest that Coping strategies not only serve to reduce stress but also become a pathway for individuals to find meaning in life and improve their quality of life. Keywords: Type 2 Diabetes Mellitus, Coping Strategies, Religious Coping, Meaning-Making, Spiritual Meaning. ABSTRAK Penderita diabetes melitus tipe 2 tidak hanya menghadapi permasalahan fisik, namun menghadapi tekanan psikologis seperti stres, kecemasan dan kualitas hidup yang menurun. Kondisi ini mendorong penderita menggunakan strategi koping yang adaptif maupun maladaptif untuk bertahan dalam menghadapi penyakitnya. Penelitian ini bertujuan untuk mengetahui bagaimana penderita diabetes melitus tipe 2 menghadapi stres dan tekanan akibat penyakitnya melalui strategi koping. Penelitian menggunakan pendekatan kualitatif dengan metode fenomenologi interpretatif, melibatkan lima partisipan berusia 40–60 tahun yang sudah terdiagnosis diabetes melitus tipe 2 dan mengalami stres. Data dikumpulkan melalui wawancara mendalam dan dianalisis dengan Coping mechanism problem-focused Coping, emotion-focused Coping serta religious Coping. Hasil penelitian menunjukkan bahwa pada awalnya penderita cenderung menolak kondisi dan merasakan emosi negatif seperti sedih, marah, dan stres. Namun seiring waktu, mereka berproses menuju penerimaan dengan menyesuaikan diri dan memaknai penyakit secara spiritual. Strategi koping yang digunakan meliputi usaha berfokus pada masalah seperti berobat rutin dan menjaga pola hidup, strategi emosional seperti menangis, pasrah, dan mencari dukungan, serta strategi religius seperti doa, pengajian, sholat, dan memaknai penyakit sebagai ujian dari Tuhan. Dukungan keluarga, pasangan, teman, serta pengalaman hidup terbukti sangat membantu dalam memperkuat ketahanan psikologis. Temuan ini menunjukkan bahwa strategi koping tidak hanya berfungsi untuk mengurangi stres, tetapi juga menjadi jalan bagi penderita menemukan makna hidup dan meningkatkan kualitas hidup mereka. Kata Kunci: Diabetes Melitus Tipe 2, Strategi Koping, Koping Religius, Pemaknaan, Pemaknaan spiritual.